Implementation and evaluation of the method “Transformative Learning through Aesthetic Experience” in Primary Education - Christou, Maria (Adult Education Critical Issues, 2023)
The purpose of this article is to present research which was held by the author regarding the implementation of the method “Transformative Learning through Aesthetic Experience”, in a group of the permanent teaching staff of Primary Education working in public schools in Athens and Piraeus, after completing their training in this method. The objectives were the following: a) to explore how teachers could effectively apply all stages of this method, in order to achieve the transformation of the stereotypical points of view of their students, and b) to investigate whether teacher training contributes to the effective implementation of the method in real teaching conditions. Firstly, it is presented the theoretical framework of this article, which focuses on five key areas: On Transformation Theory and the Constructive-Developmental Approach to Transformative Learning, the training of Primary Education teachers, the way Transformative Learning could be utilized in Primary Education, the possibility of utilizing Art as a means of developing transformative learning and on the method “Transformative Learning through Aesthetic Experience” itself. Regarding the research methodology, taking into account the purpose of the research, action research was regarded as the most appropriate and effective methodology. A presentation of the research method, the research results, a discussion, and proposals follow. It is pointed out that this article is a short presentation of the doctoral dissertation "Evaluation of the implementation of the method “Transformative Learning through Aesthetic Experience” in Primary Education", which was held by the author at the Hellenic Open University in 2016-2020. Throughout the text, gender is used, for the sake of economy of speech, without referring to any discrimination based on gender.